Coppice Growth from Tree Species Growing in an Energy Plantation : Effect of Spacing - Raizada, A.; Padmaiah, M. (Indian Forester, 1995)
The effect of tree stump spacing on sprouting and growth of sprouts was studied in four tree species (Azadirachta indica, Acacia nilotica, Leuctuma leucocephala and Eucalyptus hybrid), in a 6 and 5 year old energy plantation, growing in the semi-arid vertisols in Karnataka State. Bark thickness did not appear to be a hindrance in permitting sprouting of coppice shoots, although stump diameters were greater under wider spacing (3 × 1 m). Sprouting took place in all four species, and the optimum spacing for obtaining tall coppice shoots was 3 × 1 m for A. nilotica and L. leucocephala, and 2 × 2 m for A. indica and Eucalyptus hybrid.